Analysis of the Implementation of Sharia Principles in Human Resource Management of Islamic Cooperative - Sukmayadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the implementation of Sharia principles in human resource management, identify challenges in their application, and elucidate strategies employed by the management and administrators of the Savings and Loans and Sharia Financing Cooperative Ta’awun Sumedang to address these obstacles. Utilizing a qualitative approach, data were collected through observation, in-depth interviews, and documentation. Findings indicate that Sharia principles are integrated into human resource management through Islamic values such as trustworthiness (amanah), truthfulness (shiddiq), wisdom (fathanah), and effective communication (tabligh), which are evident in work practices, communication, training, and organizational culture. However, challenges include employees’ limited understanding of Islamic economics, insufficient training grounded in Islamic values, and an incentive system focused on quantitative targets rather than Sharia-based ethics. To overcome these issues, the cooperative implements strategies such as thematic training oriented toward Sharia principles, regular spiritual development programs, and enhancements to the performance management system that incorporate Islamic work ethics assessments. The study concludes that leadership commitment and the internalization of Sharia values are critical for optimizing human resource management aligned with Islamic principles in cooperative settings.